Electron paramagnetic resonance studies and magnetic field effects on porphyrin nanostructures and triad systems - Richert, S (2016)
The studies presented in this thesis deal with the investigation of inter- and intramolecular interactions in porphyrin nanostructures and molecular triad systems using a variety of different electron paramagnetic resonance (EPR) based techniques as well as optical spectroscopy. Dipolar and exchange couplings were investigated in a range of linear and cyclic copper-containing porphyrin nanostructures by continuous wave (cw) and pulse EPR. The magnitude of the exchange interaction, J, and trends in this property could be determined by numerical simulations of the cw EPR spectra or pulse dipolar evolution data. Using double electron-electron resonance (DEER), through-bond exchange coupling in a bis-copper six-porphyrin nanoring could directly be measured over a distance of ∼4 nm. By comparison of the results with those obtained for a singly connected but otherwise identical system, the J-coupling in this ring structure containing two identical, parallel paths was further shown to be the result of constructive quantum interference. In a ten-membered porphyrin nanoring containing two copper and eight zinc centres, the interaction between the central metals of the porphyrins and axial nitrogen ligands of different molecular templates was investigated by cw EPR, electron nuclear double resonance (ENDOR) and DEER. The weak coupling between copper and axial nitrogen ligands could be detected and it was found that the difference in binding affinity between copper and zinc to axial nitrogen ligands influences the structure of the formed complexes and preferred location of the copper centres. We were able to show that the template design allows control over the complex geometry on a molecular level. Triplet state delocalisation was investigated in a series of ladder complexes, formed between linear zinc porphyrin oligomers and bidentate nitrogen ligands, by transient cw EPR and pulse ENDOR techniques. It was found that even though the porphyrin units are held in an approximately co-planar arrangement within the ladder complex, which should favour long-range electronic communication, complete delocalisation is restricted to two porphyrin units at low temperatures and no delocalisation across the bridging ligand was observed. In a different project on symmetric and asymmetric zinc porphyrin oligomers with varying side and end groups, the influence of electronic symmetry on triplet state delocalisation was determined to be the major factor governing and limiting the extent of triplet state delocalisation in linear porphyrin oligomers. Triplet states of zinc porphyrins with different side groups have also been investigated in liquid crystal solvents by EPR. The alignment of the porphyrins is observed to depend strongly on the side groups of the porphyrin core. The orientation and conformations of the porphyrins could be obtained by simulation of the transient cw EPR spectra and order parameters were determined. The influence of small (<10 G) magnetic fields on the recombination kinetics of spin-correlated radical pairs formed upon photo-excitation of molecular triad systems was studied by transient absorption techniques. Molecular triads serve as model compounds for the study of anisotropic magnetic field effects, which could previously only be detected at comparatively high fields of >30 G. Here it is shown for the first time that hyperfine-driven magnetic field effect anisotropy is observable at magnetic fields comparable to that of the Earth (∼0.5 G), underlining the feasibility of a chemical compass for avian magnetoreception.